Novel lncRNA lncFAM200B: Molecular Characteristics and Effects of Genetic Variants on Promoter Activity and Cattle Body Measurement Traits - Zhang, Sihuan; Kang, Zihong; Sun, Xiaomei; Cao, Xiukai; Pan, Chuanying; Dang, Ruihua; Lei, Chuzhao; Chen, Hong; Lan, Xianyong (Frontiers in Genetics, 2019)
Skeletal muscle is one of the three major muscle types in an organism and has key roles in the motor system, metabolism, and homeostasis. RNA-Seq analysis showed that novel lncRNA, lncFAM200B, was differentially expressed in embryonic, neonatal, and adult cattle skeletal muscles. The main aim of this study was to investigate the molecular and expression characteristics of lncFAM200B along with its crucial genetic variations. Our results showed that bovine lncFAM200B was a 472 nucleotide (nt) non-coding RNA containing two exons. The transcription factor binding site prediction analysis found that lncFAM200B promoter region was enriched with SP1 transcription factor, which promotes the binding of myogenic regulatory factor MyoD and DNA sequence. The mRNA expression analysis showed that lncFAM200B was differentially expressed in embryonic, neonatal, adult bovine muscle tissues, and the lncFAM200B expression trend positively correlated with that of MyoG and Myf5 in myoblast proliferation and differential stages. To identify the promoter active region of lncFAM200B, we constructed promoter luciferase reporter gene vector pGL3-Basic plasmids containing lncFAM200B promoter sequences and transfected them into 293T, C2C12, and 3T3-L1 cells. Our results suggested that lncFAM200B promoter active region was from −403 to −139 (264 nt) of its transcription start site, covering 6 SP1 potential binding sites. Furthermore, we found a novel C-T variation, named as SNP2 (ERZ990081 in European Variation Archive) in the promoter active region, which was linked to the nearby SNP1 (rs456951291 in Ensembl database). The genotypes of SNP1 and combined genotypes of SNP1 and SNP2 were significantly associated with Jinnan cattle hip height. The luciferase activity analysis found that the SNP1-SNP2 haplotype CC had the highest luciferase activity, which was consistent with the association analysis result that the combined genotype CC-CC carriers had the highest hip height in Jinnan cattle. In conclusion, our data showed that lncFAM200B is a positive regulator of muscle development and that SNP1 and SNP2 could be used as genetic markers for marker-assisted selection (MAS) breeding of beef cattle.